Why was it possible to understand the quantum world? - Hüfner, Jörg (European physical journal special topics, 2020)
The question in the title is answered by analyzing a specific case, Max Planck’s discovery of the radiation law. Trial and error as method of research and a rather moderate enlargement of the “knowledge space” of classical physics had been sufficient to unravel the secrets of quantum phenomena.
Gesehen am 02.09.2021